ANALISIS NILAI-NILAI KARAKTER SISWA DALAM PEMBELAJARAN PPKn DI KELAS VII SMP SWASTA FAJAR MAS LASORI II - Hendri Yanto Laia (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
The aims of this research are 1) To find out what the character values ​​of students are in learning in class VII of Fajar Mas Lasori II Private Middle School and 2) To find out Civics learning in class VII of Fajar Mas Lasori II Private Middle School. This type of research is qualitative research using a descriptive approach. The subjects in this research were PPKn subject teachers and class VII students at Fajar Mas Lasori II Private Middle School. Data collection techniques in this research used 1) Observation Techniques, 2) Interview Techniques, 3) Documentation Techniques. The data analysis technique in this research uses 1) Data Reduction, 2) Data Presentation, 3) Conclusion Drawing. The results of this research indicate that the character values ​​of students in class VII PPKn learning at Fajar Mas Lasori II Private Middle School are good. So it can be concluded that 1) Based on the results of interviews with teachers and students presented in Chapter VI, it can be concluded that the character values ​​of class VII students at Fajar Mas Lasori II Private Middle School are good 2) The results of this research data analysis show that PPKn learning in class VII Fajar Mas Lasori II Private Middle School has been integrated with all character values. Suggestions from researchers 1) To the school, to achieve ideal student character values, it is best to implement, supervise the process, and evaluate student character values ​​in accordance with predetermined standards, not only during the PPKn learning process but at all stages of learning at school and outside school. 2) Subject teachers must continue to develop educational skills to master various methods, strategies and techniques in the learning process to achieve the predetermined character achievement indicators.